2011
DOI: 10.1055/s-0031-1275748
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients Reliant Upon Mitrofanoff Catheterisation

Abstract: Quality of life in patients dependent on Mitrofanoff catheterisation for bladder emptying is good. The SF-36 measures 8 major health care outcomes and in our patients these measures of health were similar to those seen in the general population, rather than the poorer outcomes reported in patients with other chronic medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Smith, et al evaluated 19 patients older than 16-years-old with the SF-36 health survey Version 2®. The score for Physical Functioning (PF=50.4), Role Physical (RP=53.8), Bodily Pain (BP=55.6), Vitality (VT=56.9), Social Functioning (SF=51.5), Role Emotional (RE=52.2), and Mental Health (MH=54.6) were all higher than those reported within the normal population (normal=50.0) and found the same results when compared against age-matched controls (9). This results are comparable with ours.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Smith, et al evaluated 19 patients older than 16-years-old with the SF-36 health survey Version 2®. The score for Physical Functioning (PF=50.4), Role Physical (RP=53.8), Bodily Pain (BP=55.6), Vitality (VT=56.9), Social Functioning (SF=51.5), Role Emotional (RE=52.2), and Mental Health (MH=54.6) were all higher than those reported within the normal population (normal=50.0) and found the same results when compared against age-matched controls (9). This results are comparable with ours.…”
Section: Discussionsupporting
confidence: 56%
“…Ease of catheterization had roughly been described in patients with CUD with the Mitrofanoff principle and had been more focused on the type of stoma (Umbilical, V-Quadrilateral-Z (VQZ) plasty (Figure -1) and V-Quadrilateral (VQ) flaps) being easy in most patients (5,7). Cosmesis and satisfaction had been described to be satisfactory or excellent in most patients but doing emphasis on the type of stoma (1,5,(7)(8)(9) The aim of this article is to determine HRQoL, ease of catheterization, and self-perception of global satisfaction and cosmetic outcomes in a subset of patients with CUD with the Mitrofanoff principle and to compare the results in patients with umbilical stomas and V-Quadrilateral-Z (VQZ) plasty stomas.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al assessed 19 patients over the age of 16 using the SF-36 Health Survey, version 2. Physical Functioning (PF = 50.4), Role Physical (RP = 53.8), Bodily Pain (BP = 55.6), Vitality (VT = 56.9), Social Functioning (SF = 51.5), Role Emotional (RE = 52.2), and Mental Health (MH = 54.6) all scored higher than in the normal population (normal = 50.0), and the same results were found when compared to age-matched controls [ 20 ].…”
Section: Discussionmentioning
confidence: 68%
“…The psychosocial impact of Mitrofanoff continence should not be underestimated. Successful CCUD continence can restore quality of life to levels comparable to those of the general population . Chabchoud et al.…”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial impact of Mitrofanoff continence should not be underestimated. Successful CCUD continence can restore quality of life to levels comparable to those of the general population [17]. Chabchoud et al [18] evaluated 57 patients with Mitrofanoff channels and found that a successful channel enabled 94% of patients to return to work, 79% to return to schooling (where relevant) and 83% to continue a satisfactory sex life.…”
Section: Discussionmentioning
confidence: 99%